Synergy of Survey Implementation Between PT Makara Jaya Marine and PT Biro Klasifikasi Indonesia to Improve the Quality of Survey Services - Finny Okta Safira; Eka Budi Tjahyono; Meilinasari NH; Panderaja Sijabat (Greenation Research & Yayasan Global Resarch National, 2023)
Ship survey is an implementation of ship inspection carried out by surveyors to maintain or maintain ship performance and to check endurance, strength, and feasibility on ships so that the lifetime of a ship can run optimally . The problem that occurs is conducting a joint survey activity between PT Makara Jaya Marine and PT Biro Klasifikasi Indonesia, where both companies have the same services . Then the purpose of this research is to find out the reasons for the company's cooperation and to find out the form of the system for implementing cooperation in survey activities between PT Makara Jaya Marine and PT Biro Klasifikasi Indonesia . The method used is descriptive qualitative. From the research results obtained the conclusion that the reason for the company's cooperation is because PT Biro Klasifikasi Indonesia does not have a special marine surveyor to survey offshore vessels . The form of the system for implementing cooperation in survey activities is in the form of a written contract agreement that lasts for 365 days, where PT Makara Jaya Marine as the provider of labor and PT Biro Klasifikasi Indonesia as the provider of survey services . Then Efforts made to improve the quality of survey services in this collaboration are to improve the quality of survey services, increase the number of surveyors and improve the quality of surveyors at PT Makara Jaya Marine .